Etninen heterogeenisuus ja etniset konfliktit 2003-2010 - Vanhanen, Tatu (Yhteiskuntatieteellinen tietoarkisto, 2010)
Tutkimusaineisto liittyy professori Tatu Vanhasen pitkäaikaiseen etnistä nepotismia ja etnisiä konflikteja koskevaan tutkimustyöhön. Aineisto sisältää 176 valtiota ja kolme mittaria: etninen heterogeenisuus (Ethnic Heterogeneity, EH) mittaa epäsuorasti etnisen nepotismin astetta yhteiskunnassa, institutionaalisten etnisten ristiriitojen aste (Scale of Institutionalized Ethnic Interest Conflict, IC) kuvaa väkivallattomien etnisten konfliktien merkitystä ja etnisen väkivallan aste (Scale of Ethnic Violence, EV) kuvaa väkivaltaisten etnisen ristiriitojen määrää ja laatua. Aineisto kuvaa tilannetta eri maissa vuosien 2003 ja 2010 välisenä ajanjaksona. Tiedot on kerätty erilaisista kirjallisista lähteistä. Lähteet ja muuttujien tarkka kuvaus on koottu taustatietoa-dokumenttiin. This database on the measures of ethnic heterogeneity and ethnic conflicts in 176 contemporary countries is connected with Tatu Vanhanen's long-term research project on the causal relationship between ethnic nepotism and the extent of ethnic conflict and violence in the world. The measures are: Ethnic Heterogeneity (EH) that measures to some extent the significance and potential intensity of ethnic nepotism; Scale of Institutionalized Ethnic Interest Conflict (IC) that is used to measure the estimated significance of principally nonviolent ethnic conflicts; and Scale of Ethnic Violence (EV) that is intended to measure the relative significance of violent ethnic confict in a country. The estimated scores are based on incidents during the period 2003-2010, and the database also contains brief references to the nature of conflicts. See background information for detailed information of the measures and used sources.